(untitled) (Journal of Oriental Studies, 2016)
Kazakh steppe was riddled with the Sufi ideas. Factors such as the spread of the Sufi ideas, which were founded by the Turkish poet of the Middle Ages Skin Ahmet Yasaui, religious and linguistic homogeneous team, who took the Arabic as the language of Islam, Persian as the language of poetry, Sufi borrowed motifs and images as a result of literary influences, the Islamization of indigenous beliefs on the basis of the Sufi exercises should promote the development of the Sufi poetry. However, despite the fact that the Kazakh poet, widely used in the products Sufi thesaurus, we do not find texts composed by the canons of the Sufi poetry. It was only in the 19th and 20th centuries Shakarim Qudaiberdyuly expresses his religious and philosophical outlook language Sufi poetry. In his poems Sufi motives and terms are undergoing a process of «Kazakhization» which affects the value of the Sufi elements. In this article we try to identify the causes of these changes and trends, especially the Sufi ideas of Shakarim, which can be considered representative of the Kazakh neosufizm.